Ecological effects of land-use change on two sides of the Hu Huanyong Line in China. (February 2022) - Kong, Xuesong; Fu, Mengxue; Zhao, Xiang; Wang, Jing; Jiang, Ping
Abstract: Scale and spatial pattern are two essential attributes of an ecosystem. Impacts of land-use change on the scale and spatial pattern of ecological land are not systematically well reported. This study analyzed the spatiotemporal change characteristics of ecological land on two sides of the Hu Huanyong Line (Hu Line) based on land use/cover remote sensing images of 1995, 2005 and 2015 in China. An ecological disturbance index combining scale with fragmentation changes was introduced to quantitatively evaluate the ecological consequences caused by land-use change. From 1995–2015, China's ecological land area decreased by 26.94 × 10 4 km 2, which was 4.83% of the level in 1995. The results showed that the overall intensity of ecological disturbance caused by land-use change increased over time, and significant spatial heterogeneity was found on both sides of the Hu Line. Clustered ecological land degradation coexisted with large-scale ecological restoration on the northwestern side, while multipoint farmland occupation and the distribution of the Grain for Green project caused most of the ecological land change on the southeastern side. Nine combination types of ecological consequences based on scale and fragmentation changes were identified during 1995–2015. Although the ecological land scale decreased in some counties, positive ecological consequences were found by alleviating the fragmentation of ecological land. We argue that scale-oriented conservation policies of ecological land should be replaced by cooperative conservation on an increasing scale and with optimized spatial patterns. Highlights: An index combining scale with fragmentation changes was used to evaluate ecological disturbance. The changes in ecological land on two sides of the Hu Line have obvious regional differentiation. The hot spots of ecological disturbance are closely related to those of the dynamic degree of ecological land. The ecological disturbance presents a negative effect at the county level and is dominated by weakly negative disturbance.